2022
DOI: 10.1111/jace.18529
|View full text |Cite
|
Sign up to set email alerts
|

Surface decorations to abrupt change performance, robustness, and stability of electrodes for solid oxide cells

Abstract: Solid oxide cell electrodes need to display a wide range of combined properties, for example, electronic and ionic conductivities, catalytic activity, chemical compatibility with other parts, thermal expansion match, phase stability, and tolerance to foreign species/contaminants. It is extremely challenging for a single material to meet all these features required. Surface decoration is a remarkably adaptive strategy to provide needed features to the electrodes by introducing functioning materials through vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 123 publications
(280 reference statements)
0
4
0
Order By: Relevance
“…This could be developed by controlling the particle size and sintering temperature. [48] Different researchers studied the durability and performance optimization of LSM/YSZ composite cathodes either by altering the ratio of LSM/YSZ [20,[49][50][51][52][53][54] or electrode microstructure by nanoscaling and infiltration. [55] It was shown that increasing Sr concentration up to x = 0.5 in LSM matrix for LSM-YSZ composites is advantageous for both electronic conductivity and polarization resistance.…”
Section: Lsm-based Perovskite Materials As Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…This could be developed by controlling the particle size and sintering temperature. [48] Different researchers studied the durability and performance optimization of LSM/YSZ composite cathodes either by altering the ratio of LSM/YSZ [20,[49][50][51][52][53][54] or electrode microstructure by nanoscaling and infiltration. [55] It was shown that increasing Sr concentration up to x = 0.5 in LSM matrix for LSM-YSZ composites is advantageous for both electronic conductivity and polarization resistance.…”
Section: Lsm-based Perovskite Materials As Cathodementioning
confidence: 99%
“…Chen et al and Hiraldo et al provided a comprehensive analysis of how surface modification impacts the performance of electrodes in solid oxide fuel cells for a more in-depth exploration. [54,107] According to reports, the addition of metal nanoparticles such as Ag, Pd and Pr in LSCF matrix enhances their catalytic activity including oxygen adsorption, desorption, dissociation, and diffusion due to typical properties of metal nanoparticles. [108][109][110] There is extensive research on Ag nanoparticles as additive among these additives due to their cost effectiveness and their capability to facilitate oxygen adsorption, desorption, dissociation, and diffusion.…”
Section: Lscf (La 1-x Sr X Co 1-y Fe Y O 3-δ ) Cathode Materialsmentioning
confidence: 99%
“…Advances in synthesis and processing of metal oxide nanocomposites, 1 in manufacturing of powders and ceramics, and-last but not least-in materials characterization have paved the way to engineer functional interfaces inside polycrystalline materials. [2][3][4][5][6][7] This is true for a variety of approaches that aim at tuning both the grain boundary region and the free surfaces that define the residual pores. Segregation engineering and the exsolution of admixtures, which can be introduced by the synthesis of nanomaterials as nonequilibrium solids, have attracted increasing attention in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in synthesis and processing of metal oxide nanocomposites, 1 in manufacturing of powders and ceramics, and—last but not least—in materials characterization have paved the way to engineer functional interfaces inside polycrystalline materials 2–7 . This is true for a variety of approaches that aim at tuning both the grain boundary region and the free surfaces that define the residual pores.…”
Section: Introductionmentioning
confidence: 99%